2004
DOI: 10.1055/s-2004-830354
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Therapy of Ultrashort Hirschsprung's Disease

Abstract: UHD is reliably diagnosed by an AChE reaction in native biopsy sections from the anocutaneous transitional zone and, potentially, from 3 - 4 cm above the pectinate line. As UHD is always accompanied by aganglionosis of the distal internal sphincter, an increase in AChE activity is observed in the nerve fibres of the MCCA. The therapy of choice is a partial myectomy of the distal internal sphincter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Recent studies have demonstrated the high specificity of AChE staining but with inadequate sensitivity (up to 85%) [23–25]. False negative results are mostly connected with superficial biopsies (without muscularis mucosa), immaturity of the enzyme system (found in patients under the age of 2), technical variations in staining [26], young age of patients (AChE activity characteristic for HD is observed in 83% of children under 3 months but then grows with the patient's age) [24, 27], HSCR, TCA [28, 29], and Down's syndrome [23]. Typical morphological AChE staining pictures characteristic for HD are detected only in the distal part of the large intestine (beneath the splenic flexure) because innervations of this intestinal section are different by parasympathetic fibres of the spinal cord at the S2–S4 segments.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Recent studies have demonstrated the high specificity of AChE staining but with inadequate sensitivity (up to 85%) [23–25]. False negative results are mostly connected with superficial biopsies (without muscularis mucosa), immaturity of the enzyme system (found in patients under the age of 2), technical variations in staining [26], young age of patients (AChE activity characteristic for HD is observed in 83% of children under 3 months but then grows with the patient's age) [24, 27], HSCR, TCA [28, 29], and Down's syndrome [23]. Typical morphological AChE staining pictures characteristic for HD are detected only in the distal part of the large intestine (beneath the splenic flexure) because innervations of this intestinal section are different by parasympathetic fibres of the spinal cord at the S2–S4 segments.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Also described as achalasia of the internal anal sphincter (42), UHD has been reported with an incidence as high as 13.4% in a series of children diagnosed as having HD (43). In a retrospective study, Ciamarra et al (42) reported 20 cases of children with UHD.…”
Section: Ultrashort Hdmentioning
confidence: 99%
“…[7][8][9][10] Variability in cholinergic innervation may contribute to false-negative evaluations for HD and, less frequently, to false positives. False-negative results are primarily related to the young age of patients, 8 to short or long segments of aganglionosis [11][12][13] and to HD associated with Down's syndrome. 7 Furthermore, besides typical abnormal staining, several subtle abnormal patterns of acetylcholinesterase staining have been described.…”
mentioning
confidence: 99%